An Activated Potassium Phosphate Fertilizer Solution for Stimulating the Growth of Agricultural Plants - Belov, Sergej V.; Danyleiko, Yurij K.; Glinushkin, Alexey P.; Kalinitchenko, Valery P.; Egorov, Alexey V.; Sidorov, Vladimir A.; Konchekov, Evgeny M.; Gudkov, Sergey V.; Dorokhov, Aleksey S.; Lobachevsky, Yakov P.; Izmailov, Andrey Yu (Frontiers in Physics, 2021)
The task is to develop a sustainable industrial chemical engineering technology to improve interaction between technology, plant and soil in agriculture. The signalling crosstalk between H2O2 and NO, H2O2 and Ca2+ influences plant developmental and physiological processes. Promising technologies for crop stimulation and protection are to be based on a thorough dosed environmental impact of physical factors. The low-temperature, high-frequency plasma generated via cathode high-frequency glow discharge was used for electrolysis of the low concentration aqueous solution of strong electrolyte KH2PO4 named Plasmolite. The Plasmolite solution Raman (red) scattering spectrum maximum of 1640 cm−1 was associated with hydrogen atom vibrations. The scattering spectrum bands of 875 cm−1, 930 cm−1, 1050 cm−1, and 1123 cm−1 were associated with the aqueous electrolyte solution plasma treatment. The goal H2O2 concentration was of 100 uM. The seeds were germinated in the Plasmolite based 2×10−5M KH2PO4 solution moisturizing medium for three days. Spring spelled seeds (grade "Gremme") sprouted for 92 % compared 76 % in control option. Spring rye seeds (grade “Onokhoyskaya”) sprouted for 90 % compared 75 % in control option, and the seeds sprouted percentage with a root length of more than 6 mm was about 80 % compared 50 % in control option. The Plasmolite is promising for the production of activated H2O2 for plant stimulation and protection, focusing on the K and P2O5 function as fertilizers.